Relationships between gunshot residue, damages to human body simulators caused by “Fort 9R” or “Fort 17R”, and shot distance, type of clothing: an experimental study - Perebetiuk, A. M.; Gunas, I. V.; Prokopenko, S. V.; Kozlov, S. V.; Zubko, M. D.; Перебетюк, А. М.; Гунас, І. В.; Прокопенко, С. В.; Козлов, С. В.; Зубко, Марія Дмитрівна (My University, 2023)
A comprehensive approach to the examination of a gunshot injury is due to a significant number of factors that can affect the subsequent morphological, macroscopic and microscopic characteristics of the injury. Such factors include, in particular, the type of weapon used, the distance of the shot, and the type of cartridges with which the weapon was equipped. However, factors such as the presence or absence of clothing on the injured person's body are no less important, but at the same time underestimated. One of the ways to facilitate expert work for employees of institutions dealing with gunshot injuries would be to identify relationships between the specified parameters. The most expedient way to achieve this at the moment would be to conduct an experimental study using a simulator of soft body tissues that is as close as possible to the human body. The purpose of the study was to establish correlations between the features of the deposition of the residual components of the shot, the features of damage to the simulator of the human body and the distance of the shot and the type of clothing that covered the simulator during shots from the "Fort 9R", "Fort 17R" pistols. Using the abovementioned non-lethal pistols, 120 gelatin blocks imitating the soft tissues of the human body were shot at close range, 25 and 50 cm, with further analysis of the resulting damage and parameters of the temporary cavity in accordance with generally accepted methods. Комплексний підхід до виконання експертизи вогнепальної травми обумовлений значною кількістю факторів, що можуть впливати на подальшу морфологічну макроскопічну і мікроскопічну характеристику ушкодження. Такими факторами зокрема є вид зброї, що застосовувався, дистанція пострілу, різновид набоїв яким була споряджена зброя. Проте, не менш важливими, але водночас і недооціненими є такі фактори як наявність чи відсутність одягу на тілі постраждалої особи. Одним зі шляхів полегшення експертної роботи працівникам установ, що мають справу з вогнепальними пошкодженнями було б виявлення взаємозв’язків між зазначеними параметрами. Найбільш доцільними в даний момент шляхом досягнення цього було б проведення експериментального дослідження з застосуванням максимально наближеного до тіла людини імітатора м’яких тканин тіла. Метою дослідження було встановити кореляції між особливостями відкладання залишкових компонентів пострілу, особливостями пошкодження імітатора тіла людини та дистанцією пострілу і видом одягу, що покривав імітатор при пострілах з пістолетів «Форт 9Р», «Форт 17Р». Використовуючи вищезазначені пістолети нелетальної ділі виконано відстріл 120 желатинових блоків, що імітують м’які тканини тіла людини з дистанцій впритул, 25 та 50 см з подальшим аналізом утворених пошкоджень, параметрів тимчасової порожнини відповідно до загальноприйнятих методик.
Взаємозв’язки між залишковими компонентами пострілу, пошкодженнями імітаторів тіла людини при пострілах з «Форт 9Р» і «Форт 17Р» та відстанню пострілу і видом одягу: експериментальне дослідження
Зубко М. Д. - https://orcid.org/0000-0002-3683-4010
Keywords: firearm; gunshot injury; correlations; "Fort 9R"; "Fort 17R"; вогнепальна зброя; вогнепальна травма; кореляції; «Форт 9Р»; «Форт 17Р»